The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.48550/arxiv.2201.02160
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A new photometric study of M14 (NGC 6402): An interpretation of the Horizontal Branch and beyond

M. A. Yepez,
A. Arellano Ferro,
D. Deras
et al.

Abstract: We present a CCD VI photometric study of the globular cluster M14. Particular attention is given to the variable stars. This allowed new classifications and cluster membership considerations. New variables are reported; 3 RRc, 18 SR and 1 SX Phe. The Fourier decomposition of RR Lyrae light curves lead to the mean cluster metallicity of [Fe/H] ZW = −1.3 ± 0.2. Several independent methods yield a mean distance of 9.36 ± 0.16 kpc. A Colour-Magnitude diagram outlined by the cluster members enabled a matching with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…As a result of different evolutionary sequences, the objects on the HB ARELLANO FERRO have a large range of He abundance causing the observed HB structure, particularly the color range, and the breadth; the higher the value of Y, the more luminous the corresponding ZAHB would be. Recently it has been shown that small variations in the He-burning core mass would also contribute to the observed breadth of the HB (Yepez et al 2022). Hence, the values of the L parameter employed in the present investigation may be responding to these effects, which in turn may be responsible, at least partially, of the scatter observed in the correlations.…”
Section: Discussionmentioning
confidence: 79%
“…As a result of different evolutionary sequences, the objects on the HB ARELLANO FERRO have a large range of He abundance causing the observed HB structure, particularly the color range, and the breadth; the higher the value of Y, the more luminous the corresponding ZAHB would be. Recently it has been shown that small variations in the He-burning core mass would also contribute to the observed breadth of the HB (Yepez et al 2022). Hence, the values of the L parameter employed in the present investigation may be responding to these effects, which in turn may be responsible, at least partially, of the scatter observed in the correlations.…”
Section: Discussionmentioning
confidence: 79%